Neuroprotective Effect of Chebulagic Acid via Autophagy Induction in SH-SY5Y Cells - Kim, Hee Ju (The Korean Society of Applied Pharmacology, 2014)
Autophagy is a series of catabolic process mediating the bulk degradation of intracellular proteins and organelles through formation of a double-membrane vesicle, known as an autophagosome, and fusing with lysosome. Autophagy plays an important role of death-survival decisions in neuronal cells, which may influence to several neurodegenerative disorders including Parkinson’s disease. Chebulagic acid, the major constituent of Terminalia chebula and Phyllanthus emblica, is a benzopyran tannin compound with various kinds of beneficial effects. This study was performed to investigate the autophagy enhancing effect of chebulagic acid on human neuroblastoma SH-SY5Y cell lines. We determined the effect of chebulagic acid on expression levels of autophago-some marker proteins such as, DOR/TP53INP2, Golgi-associated ATPase Enhancer of 16 kDa (GATE 16) and Light chain 3 II (LC3 II), as well as those of its upstream pathway proteins, AMP-activated protein kinase (AMPK), mammalian target of rapamycin (mTOR) and Beclin-1. All of those proteins were modulated by chebulagic acid treatment in a way of enhancing the autophagy. Additionally in our study, chebulagic acid also showed a protective effect against 1-methyl-4-phenylpyridinium (MPP(+)) - induced cytotoxicity which mimics the pathological symptom of Parkinson’s disease. This effect seems partially mediated by enhanced autophagy which increased the degradation of aggregated or misfolded proteins from cells. This study suggests that chebulagic acid is an attractive candidate as an autophagy-enhancing agent and therefore, it may provide a promising strategy to prevent or cure the diseases caused by accumulation of abnormal proteins including Parkinson’s disease.